A comparative assessment of three formulations of botulinum toxin A for facial rhytides: a systematic review and meta-analyses - Bonaparte, James P; Ellis, David; Quinn, Jason G; Ansari, Mohammed T; Rabski, Jessica; Kilty, Shaun J (Université d'Ottawa | University of Ottawa, 2013)
Abstract Background Botulinum toxin A is a commonly used biological medication in the field of facial plastic surgery. Currently, there are three distinct formulations of botulinum toxin A, each with their purported benefits and advantages. However, there is considerable confusion as to the relative efficacy and side-effects associated with each formulation. Therefore, the purpose of this paper is to systematically assess published studies and perform a meta-analysis to determine if there is a significant advantage of any of the individual formulations. Methods/design A systematic literature search was performed for all relevant English language randomized controlled trials using Embase, Cumulative Index to Nursing and Allied Health Literature (CINAHL), MEDLINE, World Health Organization (WHO) International Clinical Trials Registry Platform, European Union (EU) Clinical Trials Register, Cochrane Library databases of clinical trials, and ClinicalTrials.gov. Inclusion criteria included any randomized controlled trial (RCT) that assessed the use of botulinum toxin for cosmetic purposes. The included articles were also analyzed for bias using the Cochrane Collaboration’s tool for assessing the risk of bias in RCTs. Discussion The results of this review will provide clinicians with an unbiased, high level of evidence of the comparative efficacy of individual preparations of botulinum toxin A. Trial registration PROSPERO: CRD4201200337